Market Analysis of Textile Products Protecting Against UV Radiation (Used for Equipping Interiors, Construction and in Protective Clothing) - Wysokińska, Zofia; Czajkowski, Tomasz (Comparative Economic Research. Central and Eastern Europe, 2013)
The aim of this article is to present the results of our analysis of the European market in the field of protective textile products, based on the EUROSTAT database and our own research. The market volumes of curtains and inner roller blinds, marquees and anti-solar curtains, male clothing accessories and female clothing accessories are presented and analyzed. Initial research of supply and demand in the Polish market of textile products protecting against UV radiation is also presented and discussed.